To find the square root of 96, we can simplify it step by step.
First, we can factor 96:
96 = 16 × 6
Now, we can take the square root:
√96 = √(16 × 6) = √16 × √6 = 4√6
So, the correct response is:
4√6
Responses
64–√
6 start root 4 end root
166–√
16 start root 6 end root
46–√
4 start root 6 end root
24
24
9 answers
To find the square root of 96, we can simplify it step by step.
First, we can factor 96:
96 = 16 × 6
Now, we can take the square root:
√96 = √(16 × 6) = √16 × √6 = 4√6
So, the correct response is:
4√6
To find the cubic root of 96, we can start by simplifying it.
First, factor 96:
96 = \( 2^5 \times 3 \)
Now, to find the cubic root:
\[ \sqrt[3]{96} = \sqrt[3]{2^5 \times 3} \]
We can simplify it further:
\[ \sqrt[3]{96} = \sqrt[3]{(2^3) \times (2^2) \times 3} = \sqrt[3]{8 \times 4 \times 3} = \sqrt[3]{8} \times \sqrt[3]{12} \]
Since \( \sqrt[3]{8} = 2 \), we have:
\[ \sqrt[3]{96} = 2 \sqrt[3]{12} \]
So, the correct response is:
2 \(\sqrt[3]{12}\).
To find the cubic root of 189, we can start by simplifying it.
First, factor 189:
\[ 189 = 3^3 \times 7 \]
Now, to find the cubic root:
\[ \sqrt[3]{189} = \sqrt[3]{3^3 \times 7} \]
We can separate the parts:
\[ \sqrt[3]{189} = \sqrt[3]{3^3} \times \sqrt[3]{7} = 3 \times \sqrt[3]{7} \]
So, the cubic root of 189 is:
3 \(\sqrt[3]{7}\).
This matches the response:
3 \(\sqrt[3]{7}\).
To find the square root of 250, we can simplify it step by step.
First, we can factor 250:
\[ 250 = 25 \times 10 \]
Now, we can take the square root:
\[ \sqrt{250} = \sqrt{25 \times 10} = \sqrt{25} \times \sqrt{10} = 5 \sqrt{10} \]
So, the correct response is:
5 \(\sqrt{10}\).
To find the square root of 128, we can simplify it step by step.
First, we can factor 128:
\[ 128 = 64 \times 2 \]
Now, we can take the square root:
\[ \sqrt{128} = \sqrt{64 \times 2} = \sqrt{64} \times \sqrt{2} = 8 \sqrt{2} \]
So, the correct response is:
8 \(\sqrt{2}\).